Master class teaching advice for journalism and mass communication instructors - Roush, Chris (Rowman & Littlefield, 2018)
"Members of the AEJMC (Association for Education in Journalism and Mass Communication) Elected Standing Committee on Teaching take readers behind the scenes to explain the teaching strategies, preparation tips, exercises, and project ideas that have, in many cases, earned them university and national teaching awards"--